Brain-computer interface combined with mental practice and occupational therapy enhances upper limb motor recovery, activities of daily living, and participation in subacute stroke - Zanona, Aristela de Freitas; Piscitelli, Daniele; Seixas, Valquiria Martins; Scipioni, Kelly Regina Dias da Silva; Bastos, Marina Siqueira Campos; de Sá, Leticia Caroline Kaspchak; Monte-Silva, Kátia; Bolivar, Miburge; Solnik, Stanislaw; De Souza, Raphael Fabricio (Frontiers in Neurology, 2023)
Background: We investigated the effects of Brain-Computer Interface (BCI) combined with Mental Practice (MP) and Occupational Therapy (OT) on performance in activities of daily living (ADL) in stroke survivors. Methods: Participants were randomized into two groups: Experimental (n=23, BCI controlling a hand exoskeleton combined with MP and OT) and control (n=21, OT). Subjects were assessed with the Functional Independence Measure (FIM), Motor Activity Log (MAL) Amount of Use (MAL-AOM) and Quality of Movement (MAL-QOM). Box and Blocks Test (BBT), and Jebsen Hand Functional Tet (JHFT) for the primary outcome of performance in ADL; Fugl-Meyer assessment was used as a secondary outcome. Exoskeleton activation and the degree of motor imagery (measured as the event-related desynchronization) were assessed in the experimental group. For the BCI, the EEG electrodes were placed on FC3, C3, CP3, FC4, C4, CP4, points measured through the 10-20 EEG system. The exoskeleton was placed on the affected hand. MP was based on functional tasks. OT consisted of ADL training, muscle mobilization, reaching tasks, manipulation and prehension, mirror therapy, and high-frequency therapeutic vibration. The protocol lasted one-hour, five times a week, for two weeks. Results:There was a difference in the between baseline and post-intervention analysis for the experimental group in all evaluations: FIM (p=0.001 d=0.56), MAL-AOM (p=0.001 d=0.83), MAL-QOM (p=0.006 d=0.84), BBT(p=0.004 d=0.40), JHFT (p=0.001 d=0.45). Within the experimental group, post-intervention improvements were detected in the degree of motor imagery (p<0.001) and the amount of exoskeleton activations (p<0.001). For the control group, differences were detected for MAL-AOM (p= 0.001 d=0.72), MAL-QOM (p= 0.013 d=0.50), and BBT (p= 0.005 d=0.23), Notably, the effect sizes were larger for the experimental group. No differences were detected between groups at post-intervention. Conclusion: BCI combined with MP and OT is a promising tool for promoting sensorimotor recovery of the upper limb and functional independence in subacute post-stroke survivors.